Inquiry-Based Teaching Practices, Attitudes, and Difficulties of Secondary Science Teachers in Masinloc District Division of Zambales for S.Y. 2020-2021 - Bioco, Maricriz S.; Echaure, Jessie S. (Future Science / FSH-PH Publications, 2021)
This study aimed to assess the science inquiry-based practices, attitudes, and difficulties of secondary science teachers in the district of Masinloc, division of Zambales. The data gathered through the questionnaire were statistically treated with percentage, weighted mean, Pearson’s Correlation Coefficient, and Analysis of Variance (ANOVA). There is significant difference on the number of trainings towards origin of questioning, nature of problem, responsibility within the inquiry process, students’ diversity and variability and explanation of learning goals. There is significant difference on highest educational attainment towards explanation of learning goals and significant on sex towards origin of questioning. There is significant difference on the perception towards attitude on the use of inquiry-based teaching and learning when grouped according to highest educational attainment. There is significant difference on the number of trainings towards all dimensions of practices of science teachers exhibited components of scientific inquiry-based learning approach; The researcher recommended that the use of inquiry-based teaching and learning approach in teaching Science is highly encouraged in order to help the learners to overcome their problems in engaging with the lesson; that the teacher is encouraged to use the inquiry-based teaching and learning practices model to help them in attaining the consistency of the inquiry process within their lesson; and lastly a replication of this study is encouraged with in-depth and wider in scope so as to better determine the effectiveness of Inquiry-Based Teaching/Learning approach.